Pengaruh Green Banking dan Corporate Social Responsibility terhadap Profitabilitas pada Perbankan Syariah di Kawasan ASEAN - Rajuanto, Septian; Fahmi, Muhammad; Helmi, Syarif M (MASINTAN ACCOUNTANCY RESEARCH, 2026)
Research aims: The side effects of company expansion to increase profits lead to climate change and threats to the sustainability of the ecosystem, thus requiring a "go green" movement. Even though sharia banking does not directly fall into the category of companies that pollute, however, if banks finance companies which pollute the environment, then sharia banks also cause environmental damage. This research aims to examine the effect of green banking and corporate  social responsibility (CSR) on profitability in sharia banking in the ASEAN Region. Design/Methodology/Approach: The sample in this study was 20 Sharia banks from 4 countries that released annual reports and  sustainability reports on their respective internet sites during the observation period from 2018 to 2022 using the content analysis method. Research findings: This research finds that green banking has no effect on bank profitability, on the contrary, CSR has a positive effect on bank profitability. Thus, stakeholders can consider the influence  of green banking and CSR variables in making their decisions on the profitability of sharia banks in the ASEAN Region. Theoretical contribution/Originality: This study examines the impact of green banking and Corporate Social Responsibility (CSR) on the profitability of Islamic banks across the ASEAN region using a cross-country sample. Practitioner/Policy implication: The findings offer practical and policy implications by assisting Islamic banks in the ASEAN region to improve profitability through green banking practices, stakeholder engagement, and sustainability disclosures aligned with international standards. They also support regulators, particularly in Indonesia, in developing standardized green banking policies to enhance the long-term performance of Islamic banks.